The Effect of Classical Music Therapy on Sleep Disorders of Children Hospitalized at Sakinah Islamic Hospital Mojokerto Regency - Tri Ratnaningsih; Desi Arista (Journal of Ners and Midwifery, 2020)
The general response that occurs when hospitalized children included regression, anxiety separation, apathy, fear, and sleep disorders. One method for improving sleep was music therapy. This research aimed to prove the effect of classical music therapy on sleep disorders at children who have experienced hospitalization at Sakinah Islamic Hospital, Mojokerto Regency. This research design was pre-experimental with one group pretest-post test design approach. The population at this research were all children who experienced hospitalization at Sakinah Islamic Hospital at Mojokerto Regency on February 26th-March 21th 2019 as many as 43 children. The sampling technique of this research was purposive sampling. The sample size that met the research criteria were 30 children. The research instrument used SOP music therapy and questionnaires. The results of this research suggested that before being given music therapy almost all respondents had lacked sleep needs as many as 23 respondents (76.7%), and after being given music therapy almost entirely had equal sleep needs as many as 26 respondents (86.7%). Wilcoxon Signed Rank Test suggested that pvalue = 0,000 or <Î± (0,05), which meant that there was an effect of music therapy on sleep disorders at children who have been hospitalized at Sakinah Islamic Hospital Mojokerto Regency. Music therapy would provide a relaxing effect where when children like music would stimulate endorphins to provide a sense of calm and easier to sleep.